THE CORRELATION BETWEEN HIDDEN ECONOMY AND MONEY LAUNDERING IN IRAQ 2012-2022 - pcadmin, Dr. FatimahFaraj Saad; Dr. Zeinab Ali Dashoor (Scholar Express Journals, 2024)
The emergence of hidden economy and money laundering in Iraq resulted from the accumulation of long years of wars and unstable political and economic conditions. However, this phenomenon increased after 2003 due to the radical changes that happened in Iraq, including the great openness of borders to abroad, the absence of government control over imports, and the flow of funds without any control or accountability, in addition to the spread of administrative and financial corruption that led to increasing hidden economy and money laundering, which impacted the Iraqi economy. The research problem of the present study is manifested in the increasing magnitude of hidden economy in Iraq and the consequent increase in illicit income, which contributes to an increase in money laundering operations. The present study aims to estimate the magnitude of hidden economy and money laundering in Iraq from 2012 to 2022. The results of the present study reveal that the high magnitude of hidden economy in Iraq is due to low levels of domestic production of goods in the public sector as a result of the interruption of most production lines due to the widespread destruction of state companies. The present study recommends that it is important to combat administrative and financial corruption and enhance the role of public integrity by all possible means, as corruption is one of the core reasons contributing to the spread of the phenomenon of hidden economy and money laundering in Iraq.
Keywords: Hidden Economy; Money Laundering; parallel economy